PENGARUH METODE PEMBELAJARAN GROUP INVESTIGATION (GI) TERHADAP HASIL BELAJAR SISWA MATA PELAJARAN AGRIBISNIS TANAMAN SAYURAN DI KELAS XI SMK NEGERI 2 SOPPENG - Sultamin, Muhammad Sulhan; Rais, Muhammad; Nurmila, Nurmila (Jurnal Pendidikan Teknologi Pertanian, 2018)
This research is a pre-experimental study using a quantitative approach that aims to determine the effect of Group Investigation learning methods on student learning outcomes at XI ATPH SMK Negeri 2 Soppeng in 2018/2019 school year consisting of three classes with a population of 60 students. The sample in this study is the XI.C ATPH class of SMK Negeri 2 Soppeng with a total of 19 students. Samples were taken by purposive sampling. The data collected are learning outcomes of Vegetable Plant Agribusiness. The form of learning outcome test used is an essay. Data were analyzed using descriptive statistics. The results showed that there was an effect of Vegetable Plant Agribusiness learning outcomes. This is indicated by the sig value (0,000 <0,05) and supported by differences in learning outcomes before learning (63,3) in the very low category and after learning (85,8) in the high category. This means that the effect produced is in a significant category. The conclusion is that the Group Investigation learning method affects the learning outcomes of Vegetable Plant Agribusiness.